Long-term outcome and predictors of outcome in patients with non-ischemic dilated cardiomyopathy. (1st October 2016) - Karatolios, Konstantinos; Holzendorf, Volker; Richter, Anette; Schieffer, Bernhard; Pankuweit, Sabine; ,
Abstract: Background: The study objectives were to identify predictors of outcome and to assess the long-term outcome in patients with non-ischemic dilated cardiomyopathy (DCM). Methods and results: From 2004 to 2008, 206 consecutive patients (age 52.1 ± 12.6 years) with non-ischemic DCM were prospectively enrolled in the study and followed up for a mean of 55.6 ± 18.4 months. Predictors of outcome were identified in a multivariable analysis with a Cox proportional hazards analysis. The primary endpoint was a composite of all-cause mortality or heart transplantation. During the follow-up period 47 patients died (22.8%) and 5 patients (2.4%) underwent heart transplantation for end-stage heart failure. For the primary end point, a systolic LVEF < 35% (hazard ratio 2.56; 95% confidence interval 1.21–5.45; p  = 0.014), a prolonged QTc interval > 440 ms (hazard ratio 2.56; 95% confidence interval 1.24–3.83; p  = 0.007) and a GFR < 60 ml/min/1.73 m 2 (hazard ratio 2.42; 95% confidence interval 1.36–4.29; p  = 0.003) were identified as independent predictors, whereas the presence of an LBBB, atrial fibrillation, mild mitral regurgitation or treatment with digitalis were not significantly related to outcome. Conclusions: In patients with non-ischemic DCM, a reduced systolic LVEF < 35%, a prolonged QTc interval > 440 ms and an abnormal renal function with a GFR < 60 ml/min/1.73 m 2 are independent predictors of death or need for heart transplantation.